THE INFLUENCE OF PREY AND PREDATOR DENSITY ON THE PREDACIOUS BEHAVIOR OF Chrysoperla mutata (MACLACHLAN) LARVAE FEEDING ON DUBAS NYMPHS Ommatissus lybicus DEBERG - حمد, باسم; الراوي, محمد (Iraqi Journal of Science, 2024)
The functional response of Chrysoperla mutata (MacLachlan) larvae that dealt with different prey densities was Type 2. The coefficient of attack and handling time connected with changing occurred through the development of predator and prey or by increasing the capture efficiency of predator and defense efficiency of prey. The coefficient of attack increased with the increasing size of predator and with the decreasing size of prey. Also the handling time increases with the decreasing size of predator and with the increasing size of prey . Concerning the effect of predator density on the efficiency of searching, the results revealed a decrease in efficiency with increasing of number of predators due to interference and cannibalism.